Assistive Technology for Dyslexia Students in Elementary School - Rosita, Tita; Nurihsan, Juntika; Juhanaini, Juhanaini; Sunardi, Sunardi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Technological advances require collaboration in classroom learning practices by providing accessibility to optimize student learning. Classroom learning should be able to accommodate all student learning needs, including students with dyslexia. The purpose of this study was to analyze the need for assistive technology for learning innovation in one of the students who experienced dyslexia in elementary school. This research is qualitative research, using case study method. Data was collected by using interview, observation, and documentation methods. The instruments used in collecting data include: interview guidelines, observation sheets, and documentation guidelines. Data analysis was carried out in a qualitative descriptive manner. The results showed that one of the dyslexic students who is currently in fifth grade elementary school has a phonological deficit and needs learning media to help him practice increasing phonological awareness. Therefore, assistive technology-based learning media is needed to improve the quality of education for dyslexic students, especially in the training process to increase their phonological awareness.